Moyamoya Disease dan Neuromyelitis Optica: Sebuah Laporan Kasus Langka dengan Tantangan Diagnosis dan Tata Laksana - Hardiati, Rahmi Hijriani; Kholida, Baiq Hilya Kholida; Arigi, Lalu Ahmad Gamal (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2026)
Introduction: Moyamoya disease is a cause of stroke in young people with a low prevalence. Neuromyelitis optica (NMO) is also a rare disease with a low incidence.This combination of the two is extremely rare, making it an interesting case. This case report aims to report an incident of Moyamoya Disease that occurred together with Neuromyelitis optica (NMO). Case Illustration: A 37-year-old female patient presented with slurred speech, facial asymmetry, vertigo, blurred vision, and strabismus, all of which occurred suddenly. An MRI revealed partial stenosis of the right vertebral artery, right ACA, right and left MCA arteries, as well as total stenosis of the right and left ACA, right and left MCA arteries. White matter lesions were also found in the right frontal lobe, left parietal lobe, internal capsule, anterior commissure, pons, pontine tegmentum, mesencephalon, and substantia nigra. Hyperintensity lesions were also found in the spinal cord at levels C2-C6. CSF examination revealed a predominance of PMN cells. Based on the history and examination, the patient was diagnosed with Moyamoya Disease and NMO. Treatment consisted of several oral therapies, which showed improvement in complaints of limb weakness, but other complaints did not improve. After several days, the patient's condition worsened so IVIG was planned for treatments. Discussion: There are only three case reports documenting the occurrence of both diseases. The mechanism involved is antibodies, specifically anti-SSA, which contribute to the coexistence of NMO and moyamoya disease. Clinical implications, NMO make accelerating progression of moyamoya disease and leading to ischemic. Conclusion: The patient in this report was diagnosed with moyamoya and NMO. The coexistence of these two diseases necessitates a thorough examination and consideration of the coexistence of multiple diseases in patients with multiple neurological symptoms.